Operations now :Profitability,processes,performance - Finch, Byron J. ([S.l.] : Irwin Professional Pub, 2004)
"Operations Now" introduces operations from a vantage point that encompasses both the entire organization and the broader supply network. The author begins his discussion of operations management by first establishing the goal to which any high quality operation must aspire: the goal of profitability. "Operations Now" presents operations within a context that acknowledges its interactions both within all functional areas of an organization as well as the supply chain network serving it. Thus, students not majoring in operations management immediately understand why they are studying a subject that had previously seemed to them irrelevant; operations majors receive valuable instruction in how their chosen field affects and facilitates other functional areas within the enterprise and aligns with the overall goals of the organization.
Keywords: management,production management